2017
DOI: 10.1002/ajpa.23167
|View full text |Cite
|
Sign up to set email alerts
|

Does cortical bone thickness in the last sacral vertebra differ among tail types in primates?

Abstract: Results indicate that, in the context of phylogenetic clade, measures of cortical bone cross-sectional thickness can be used to allocate extinct primate species to tail type categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
(118 reference statements)
2
1
0
Order By: Relevance
“…Using a pilot data subset, a power analysis (PS v3.0.43; Dupont and Plummer, ) of two trabecular bone variables that highly influence trabecular bone strength (degree of anisotropy and bone volume fraction; Goldstein et al, ; Turner et al ; Turner, ; Ulrich et al ) indicated that six sacra per species afforded the power to detect a 20% difference between taxon means ( p < 0.05). Previous studies have found that statistically significant differences among trabecular variables can be detected using comparable numbers of primate individuals (e.g., MacLatchy and Müller, , n = 5 per group; Ryan and Ketcham, , n = 1–10 per group), and the present primate CT sample has been shown to significantly differ in measures of trabecular (Russo, ) and cortical (Nishimura and Russo, ) bone structure in the distal sacrum in relation to tail length and prehensility. While this study aimed to examine at least six sacra per taxon (Table ), sufficient museum material was not always available and some sacra had to be excluded from analyses because scans revealed internal bone damage (see also Russo, ; Russo, ; Nishimura and Russo, ).…”
Section: Methodssupporting
confidence: 64%
See 1 more Smart Citation
“…Using a pilot data subset, a power analysis (PS v3.0.43; Dupont and Plummer, ) of two trabecular bone variables that highly influence trabecular bone strength (degree of anisotropy and bone volume fraction; Goldstein et al, ; Turner et al ; Turner, ; Ulrich et al ) indicated that six sacra per species afforded the power to detect a 20% difference between taxon means ( p < 0.05). Previous studies have found that statistically significant differences among trabecular variables can be detected using comparable numbers of primate individuals (e.g., MacLatchy and Müller, , n = 5 per group; Ryan and Ketcham, , n = 1–10 per group), and the present primate CT sample has been shown to significantly differ in measures of trabecular (Russo, ) and cortical (Nishimura and Russo, ) bone structure in the distal sacrum in relation to tail length and prehensility. While this study aimed to examine at least six sacra per taxon (Table ), sufficient museum material was not always available and some sacra had to be excluded from analyses because scans revealed internal bone damage (see also Russo, ; Russo, ; Nishimura and Russo, ).…”
Section: Methodssupporting
confidence: 64%
“…Previous studies have found that statistically significant differences among trabecular variables can be detected using comparable numbers of primate individuals (e.g., MacLatchy and Müller, , n = 5 per group; Ryan and Ketcham, , n = 1–10 per group), and the present primate CT sample has been shown to significantly differ in measures of trabecular (Russo, ) and cortical (Nishimura and Russo, ) bone structure in the distal sacrum in relation to tail length and prehensility. While this study aimed to examine at least six sacra per taxon (Table ), sufficient museum material was not always available and some sacra had to be excluded from analyses because scans revealed internal bone damage (see also Russo, ; Russo, ; Nishimura and Russo, ).…”
Section: Methodssupporting
confidence: 64%
“…While the cofounders of the DLC, Dr. John Buettner-Janusch and Dr. Peter Klopfer, ran research programs focused on genetics and behaviour respectively, the DLC's unique resources have provided data for a wide variety of scientific fields, including anatomy and physiology [e.g., [3][4][5][6], social ecology [e.g., [7][8], cognition [e.g., 9-10, biomechanics [e.g., [11][12], molecular biology [e.g., [13][14], and palaeontology [e.g., [15][16][17][18]. The importance and rarity of the animals housed at the DLC necessitates thorough and effective use in educational and research initiatives, and this spirit of efficiency extends to treatment of deceased individuals.…”
Section: Introductionmentioning
confidence: 99%